OPPORTUNITIES FOR TOURIST CONECTION MUNICIPALITIES MALI ZVORNIK AND ZVORNIK, AS A FORM OF STRENGTHENING CROSS-BORDER COOPERATION BETWEEN SERBIA AND BOSNIA & HERCEGOVINA - Vuković, Predrag; Cecić, Nataša; Arsić, Slavica (Economics of Agriculture, 2011)
The paper insists on the fact that it is necessary that the municipality of Zvornik in Bosnia and Mali Zvornik in the Republic of Serbia, acting in the market as a unique tourist destination. In this sense, emphasis is placed on complementarity in all marketing and strategic management steps, policies, plans and organization of tourism. The priority goal ahead of the two brotherly municipalities, is to clearly present the natural and anthropogenic resources to enrich the tourist with adequate performance and organization. The emphasis of the offer must be placed in an appropriate quality of service and marketing and management approach as an imperative request, to market resources and valorise. It is necessary that declarative long-standing support for the development of tourism practically comes to life and multiplied the effects that tourism brings to the overall economic and social life, it is realistic to expect investors will quickly return. The aim is therefore to highlight the potential strategic directions for the future development of tourism in Mali Zvornik municipalities in Serbia and Zvornik in Bosnia with an emphasis on the implementation of integrated marketing and management approaches in the tourism market. With the right to expect that if the obvious great potential for further tourism development and assess the practical, contribute to the development of the entire area that is today from a number of reasons, is burdened with many negative tendencies.